Himpsel, Franz oral history transcript - Himpsel, Franz (My University, 2009)
Transcript of an oral history with Franz Himpsel, co-director and user of, the Synchrotron Radiation Center. Conducted by Eric Verbeten.
Keywords: Synchrotron, Himpsel